Definition of quality indicators of dairy-protein concentrates in the storage process - Gnitsevych, Victoriya; Yudina, Tatiana; Deinychenko, Liudmyla; Nykyforov, Radion; Nazarenko, Iryna (My University, 2018)
The aim of this article is to investigate changes in the structure, color and microbiological parameters of milk-protein concentrates (MPC) made of buttermilk with the use of cranberry or viburnum purees in the process of storage. Necessary results were obtained after analyzing phase transitions, changes in color-parametric and microbiological characteristics of the studied products.
Keywords: кафедра технології ресторанної і аюрведичної продукції; preservation of quality; milk-protein concentrates; differential scanning calorimetry; color-parametric characteristics; microflora; storage; збереження якості; молочно-білкові концентрати; диференціальна скануюча калориметрія; кольропараметричні характеристики; мікрофлора; зберігання